Sports fundraising : dynamic methods for schools, universities and youth sport organizations - Kelley, David J. (New York : Routledge, 2012)
"Sports Fundraising is a complete introduction to fundamental principles and best practice in sports fundraising. Focusing on the particular challenges of fundraising in intercollegiate and interscholastic sport, and for youth sport organizations, the book is designed to help students develop the professional skills that they will need for a successful career in sports or education administration." -- Back Cover
Sports fundraising : challenges and prerequisites -- Fundraising organization -- Personal skill set development in fundraising -- Dynamic fundraising essentials and principles -- Intercollegiate relationship cultivation and stewardship in fundraising -- Youth and interscholastic relationship cultivation and stewardship -- Leveraging points of sale and profit-making for fundraising success -- Working with diverse constituencies : cultivation strategies and essential resources -- Youth / interscholastic grantsmanship opportunities and approaches for success -- The future of sports fundraising : data-driven methodologies and curriculum development in higher education.
Includes bibliographical references and index.
Keywords: Sports -- Public relations; Fund raising; School sports -- Finance; College sports -- Finance